Assessing the role of strategy and socioeconomic heritage for rapidly growing firms: evidence from Germany. (19th January 2010) - Wyrwich, Michael
The present paper sheds light on how growth of young firms is affected by expansive strategies and the socioeconomic heritage of their main actors. 'Socioeconomic heritage' has to do with socialisation, prior socioeconomic circumstances and regional growth conditions; the term is elaborated upon and further defined in this study. The empirical analysis is carried out both for West Germany – a mature market economy – and for East Germany, which operated under a centrally planned economy until German reunification in 1990. The main finding of the paper is that the involvement of West Germans in East German start-ups has a favourable effect on these firm's chances of growing rapidly. This effect is attributed to the fact that West Germans are more likely to possess person-related and situation-related factors necessary for growing a business in a market economy. The results are more ambiguous as to the influence of expansive strategies on fast growth.